Initial Proteomics Analysis of Differentially Expressed Proteins from Mycoplasma gallisepticum Vaccine Strains ts-11 and F Detected by Western Blotting - Collier, S.D.; Pharr, G.T.; Branton, S.L.; Evans, J.D.; Leigh, S.A.; Felfoldi, B. (International Journal of Poultry Science, 2006)
Mycoplasma gallisepticum (MG) is the causative agent of chronic respiratory disease in layer chickens. The live MG vaccine strains that are available for use in layer chickens include F, ts-11 and 6/85. The MG vaccine strains ts-11 and 6/85 are safer than F and they have little or no potential of spreading from bird to bird. However, ts-11 and 6/85 appear to be less efficacious than F-strain. Results from studies suggest that the use of MG vaccine strain F in replacement flocks over a period of time results in the displacement of the original field strain. Also, reports of MG breaks in layer flocks previously vaccinated with ts-11 or 6/85 have resulted in revaccination of these flocks with F. The continued use of F-strain in displacement and revaccination regimens necessitates the development of more rapid and sensitive field tests that will differentiate between wild-type and vaccine strains of MG. In the present study, ts-11 and F-strain whole cell extracts were analyzed by Western blotting and proteomic methodologies. Differentially expressed protein bands were excised, in-gel digested with trypsin, and analyzed by mass spectrometry. The proteins were identified as internal proteins and were predicted to be involved in such cellular processes as carbohydrate transport and metabolism, energy production and conversion, posttranslational modification, protein turnover, chaperone activity, transcription, and translation. The results of this study suggest that proteomics may aid in the characterization of proteins that could contribute to the development and improvement of current MG diagnostic tests.